2008 2nd Annual IEEE Systems Conference 2008
DOI: 10.1109/systems.2008.4519016
|View full text |Cite
|
Sign up to set email alerts
|

Systems Thinking as an Emergent Team Property: Ongoing research into the enablers and barriers to team-level systems thinking

Abstract: -This paper describes ongoing research exploring systems thinking at the team level. Termed collaborative systems thinking by the authors, the concept of higher level systems thinking is envisioned as a means both to build workforce competency and to explicitly deal with system complexity at a higher level within an organization. This paper introduces the key research questions, an initial definition of collaborative systems thinking, demographic and technical motivators, and summarizes the research progress t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
11
0

Year Published

2009
2009
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 18 publications
(11 citation statements)
references
References 25 publications
0
11
0
Order By: Relevance
“…He surmised, "The growing body of research on EI (emotional intelligence) would support the notion of the relationship to performance as universal" (Boyatzis, 2009, p. 62). Other research priorities might include gaining more understanding of how systems thinking affects project performance, perhaps building on Skarzauskiene's (2010) findings, and on the nature, development, and assessment of systems thinking shills in individuals and project teams (Richmond, 1993;Frank, 2006Frank, , 2010Lamb and Rhodes, 2008).…”
Section: Discussionmentioning
confidence: 99%
See 4 more Smart Citations
“…He surmised, "The growing body of research on EI (emotional intelligence) would support the notion of the relationship to performance as universal" (Boyatzis, 2009, p. 62). Other research priorities might include gaining more understanding of how systems thinking affects project performance, perhaps building on Skarzauskiene's (2010) findings, and on the nature, development, and assessment of systems thinking shills in individuals and project teams (Richmond, 1993;Frank, 2006Frank, , 2010Lamb and Rhodes, 2008).…”
Section: Discussionmentioning
confidence: 99%
“…Engineered systems' complexity continues to increase, introduced through advancements in technology and the logistics required to design and field systems (Lamb and Rhodes, 2008). Q. Dong (1999) (as cited in Lamb and Rhodes, 2008) reported that with complexity increases, an ever-smaller fraction of the design knowledge is documented.…”
Section: Cross-cultural Competenciesmentioning
confidence: 99%
See 3 more Smart Citations